Cinacalcet adherence in dialysis patients with secondary hyperparathyroidism in Lombardy Region: clinical implications and costs - Alessandro Roggeri; Ferruccio Conte; Carlotta Rossi; Mario Cozzolino; Carlo Zocchetti; Daniela Paola Roggeri (BioExcel Publishing Ltd, 2020)
Background: Patients on dialysis often have secondary hyperparathyroidism (SHPT), a disorder associated with renal osteodystrophy, progressive vascular calcification, cardiovascular disease, and death. The objective of this retrospective observational study was to evaluate, in dialysis patients with SHPT, the impact of different levels of adherence to cinacalcet therapy on hospitalisations and direct healthcare costs charged to the Lombardy Regional Health Service (Italy). Methods: Data recorded in the administrative databases on all citizens undergoing dialysis between 1 January 2011 and 31 December 2011 were selected. For the aim of this study, patients with SHPT already on dialysis in the first 6 months of 2009 who had been treated with cinacalcet for at least 365 days were selected and retrospectively analysed through to end of 2012. Healthcare resource utilisation, cinacalcet adherence, and costs for medication, hospitalisations, and diagnostic/therapeutic procedures were estimated. Results: A total of 994 patients were identified (mean age 63.0 years, females 43.5%). The first patient tertile had an adherence to cinacalcet of <64.1%, whereas the third had an adherence of over 91.5%. Patients in the third adherence tertile experienced fewer all-causes hospitalisations than those in the first tertile (−19.2%; p=0.01423), fractures (−37.1%; p=0.59422), cardiovascular disease (−23.8%; p=0.04025), and sepsis (−32.3%; p=0.01386). The increase in costs for cinacalcet-adherent patients is almost completely offset by the reduction in costs for hospitalisations. Conclusions: The results of the analysis suggest that there may be some correlation between a high level of cinacalcet adherence and a decrease in hospitalisations.